Thermal relationships and exercise physiology in anuran amphibians: Integration and evolutionary implications - Navas, Carlos A.; Gomes, Fernando R. [UNESP]; Carvalho, Jose Eduardo [UNESP] (Elsevier B.V., 2008)
Thermal and water balance are coupled in anurans, and species with particularly permeable skin avoid overheating more effectively than minimizing variance of body temperature. In turn, temperature affects muscle performance in several ways, so documenting the mean and variance of body temperature of active frogs can help explain variation in behavioral performance. The two types of activities studied in most detail, jumping and calling, differ markedly in duration and intensity, and there are distinct differences in the metabolic profile and fiber type of the supporting muscles. Characteristics of jumping and calling also vary significantly among species, and these differences have a number of implications that we discuss in some detail throughout this paper. One question that emerges from this topic is whether anuran species exhibit activity temperatures that match the temperature range over which they perform best. Although this seems the case, thermal preferences are variable and may not necessarily reflect typical activity temperatures. The performance versus temperature curves and the thermal limits for anuran activity reflect the thermal ecology of species more than their systematic position. Anuran thermal physiology, therefore, seems to be phenotypically plastic and susceptible to adaptive evolution. Although generalizations regarding the mechanistic basis of such adjustments are not yet possible, recent attempts have been made to reveal the mechanistic basis of acclimation and acclimatization. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Acclimation; Acclimatization; Anurans; Calling; Exercise; Locomotor performance; Temperature